Menanamkan Wawasan Islam Moderat Melalui Pendidikan Akidah Ahlussunnah Wal Jama’ah An-Nahdiyah: Belajar dari Pendidikan Pesantren - Segaf Baharun; Sodikin (Adabuna)
Fostering moderation of Islam in the era of disruption is very urgent to face a multicultural society. Correct understanding of aqidah is the main key to maintaining inter-religious tolerance. Aqidah ahlussunah wal jama'ah an-nahdliyyah developed in Islamic boarding schools has succeeded in creating a moderate society. The results of this study indicate that moderate Islamic insight is built on aqidah ahlussunah wal jama'ah an-nahdliyyah education. This Aqidah is then synergized with the teachings of Tawhid, Fiqh, Morals and Sufism. The tradition of Islamic scholars' thought in the archipelago also contributes to strengthening moderate Islamic insights